A study on performance analysis at counter service: A case study at Employees’ Provident Fund (EPF) of Kota Bharu / Nik Nur Fatin Fatihah Sapri - Sapri, Nik Nur Fatin Fatihah (Bachelor of Science (Hons) Statistics, 2015)
A study was conducted to analyze the performance of service counters at Employees’ Provident Fund (EPF) of Kota Bharu. The aims of this study are to determine the average waiting time spend by a customer in the queue, the average waiting time spend by a customer in the system and as well as to find the optimum number of service counters that need to be opened. The study used a secondary data which was taken from Services Section that was given by Encik Ramdzi Bin Ismail, the Head of Services Section. The analysis used data of 20 working days in August 2014. The system uses is multichannel single phase system. The study applies Queueing theory of waiting lines. There are nine services offered which are EPF statement, Housing, Non-housing, Typical Citizen, Employers Registration, Members Registration, Complaints/Warrants/i-account/Tpin, Inquiry and Payment Transaction. The findings of the study reveal that the transaction in August 2014 show a declining pattern. Payment transaction and Employers Registration transaction are found to be the highest and lowest transaction in August 2014 respectively. The value of arrival rate, service rate, the average waiting time in the queue and in the system, the average number of customers in the queue and in the system, the probability of server utilization and the probability that the system is idle were calculated. The average number of customer in the queue is ranged from 2 to 59 customers per hour while the average number of customer in the system is ranged from 9 to 68 customers per hour. Apart of that, the findings of the study also show that the average waiting time spend by a customer in the queue is ranged from 0.06 hours (3.6 minutes) to 0.95 hours (57 minutes). Meanwhile, the average waiting time spend by a customer in the system is ranged from 0.2 hours (12minutes) to 1.12 hours (67.2 minutes). It is recommended that the optimum number of servers that need to be opened are 8 servers. This type of study is suitable to be applied in other departments that have a similar operation as EPF and some recommendations are recommended for further study